Using Full Duality to Show that Simultaneously Additive Direct and Indirect Utilities Implies Unitary Price Elasticity of Demand - Samuelson, Paul A. (Econometrica, 1965)
Paul A. Samuelson, Using Full Duality to Show that Simultaneously Additive Direct and Indirect Utilities Implies Unitary Price Elasticity of Demand, Econometrica, Vol. 33, No. 4 (Oct., 1965), pp. 781-796